Strategi Pemasaran Digital melalui Media Sosial pada UMKM Bakery - Victor Diwantara; Sella Murdini; M. Nazori (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the social media-based marketing strategies implemented by MSME Bakery in developing its business. The study employed a qualitative case study method using observation, in-depth interviews, and documentation. The results indicate that consistent use of WhatsApp and Facebook has positively impacted sales, market reach, and customer loyalty. However, challenges such as limited digital skills and time management for content creation still exist. These findings suggest that social media is an effective marketing tool for MSMEs when supported by proper content strategies and digital literacy.